Electroconductive gel abrasive having ferrous sulfate slow release function and electrofenton polishing method
Patent Information
- Application Number
- CN202510955766.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-11
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-07-11
AI Technical Summary
然而,干法混合工艺存在明显的局限性:一方面,由于范德华力的作用,微纳米级磨料极易发生团聚,导致磨具内部磨料分布不均;另一方面,磨具表面形成的团聚颗粒在加工过程中会脱落,造成工件表面划伤等二次损伤问题
[0006]与现有技术相比,本申请的具有硫酸亚铁缓释功能的导电凝胶磨具通过多尺度结构设计和功能化改性,可以实现对硬脆工件的高效环保抛光,在精密加工领域具有重要的工程应用价值。具体而言,本申请的导电凝胶磨具采用三维铜丝网络作为导电骨架,通过精密编织工艺构建连续电子传输通道,并在此基础上浇筑混合浆料,使得磨具具有均匀导电特性;其中,混合浆料中配置有硫酸亚铁缓释复合微粒,其根据特定的组分配方,并按照特定的方法步骤制备而成,具有独特的“核-壳”结构:以高比表面积活性炭为载体吸附硫酸亚铁作为反应核心,外层通过溶胶-凝胶法包覆纳米二氧化硅形成可控释放屏障。使用本发明的导电凝胶磨具进行电芬顿抛光时,机械剪切力和化学侵蚀作用会选择性破坏复合微粒表层的二氧化硅包覆层,实现硫酸亚铁的梯度释放,持续为电芬顿反应提供亚铁离子催化剂;释放的Fe2+与阴极原位生成的H2O2构成均相芬顿体系,在抛光界面产生大量高活性羟基自由基,这些强氧化性活性物质能快速软化硬脆工件表面,形成厚度约10-200 nm的改性层(此时,硬脆工件表面硬度可降低50%以上),再由导电凝胶磨具刮除,这种表面软化-机械去除的协同作用机制,显著提升了对硬脆工件的去除效率。
Smart Images

Figure CN120572473B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of precision machining, grinding and polishing, and specifically relates to a conductive gel abrasive with ferrous sulfate slow-release function and an electro-Fenton polishing method using the abrasive. Background Technology
[0002] Currently, free abrasive polishing technology remains the primary method for achieving micro- and nano-level precision on workpiece surfaces. While this method yields excellent surface quality, it generally suffers from inherent drawbacks such as low processing efficiency, low abrasive utilization (typically below 30%), and environmental pollution from polishing fluids. To overcome this technological bottleneck, researchers have developed bonded abrasive tools, employing a dry mixing-powder pressing process. By bonding the abrasive within the matrix, it significantly improves abrasive utilization and processing efficiency. However, the dry mixing process has significant limitations: on the one hand, due to van der Waals forces, micro- and nano-sized abrasives are prone to agglomeration, leading to uneven abrasive distribution within the tool; on the other hand, agglomerated particles formed on the tool surface can detach during processing, causing secondary damage such as scratches on the workpiece surface. To address these technical challenges, an innovative semi-bonded abrasive tool—gel abrasive—has been developed based on bonded abrasive tools. This tool employs a wet mixing-gel molding process, utilizing the sol-gel transition characteristics to achieve uniform dispersion of the abrasive within a three-dimensional network structure (dispersion uniformity can reach over 90%). This new type of abrasive not only inherits the high-efficiency processing advantages of bonded abrasives, but also reduces environmental pollution by decreasing the amount of polishing fluid used, while significantly improving the surface finish of workpieces, reducing the thickness of the surface damage layer by 30%-50%. For example, invention patent CN112123223A proposes a high-precision polishing ceramic-bonded abrasive using a gel injection molding process; invention patent CN108081159A proposes an organic gel molding method based on polyvinyl acetal resin; and invention patent CN120038677A proposes a high-porosity ceramic-bonded diamond micro powder abrasive. All of these demonstrate that abrasives prepared by the sol-gel method with uniform abrasive grain distribution and adjustable height can achieve nanoscale ultra-smooth surfaces when processing materials such as cemented carbide and optical glass. However, for processing hard and brittle workpieces (such as silicon carbide and sapphire), relying solely on the mechanical removal action of diamond abrasive grains still presents a significant efficiency bottleneck. To address this, researchers proposed a synergistic processing strategy involving chemical mechanical polishing (CMP). By introducing chemical reactions during the process, this strategy significantly improves the removal efficiency of hard and brittle workpieces. This mechanochemical synergistic mechanism provides important insights for developing next-generation high-efficiency precision machining technologies.
[0003] In the field of precision machining of hard and brittle workpieces, chemical mechanical polishing (CMP) technology is widely used due to its excellent surface finish. Among these, electro-Fenton polishing, as an emerging advanced oxidation processing technology, exhibits unique material removal advantages by coupling the electrochemical process with the Fenton reaction mechanism. The core of this technology lies in utilizing an electrochemical cathodic reduction reaction to generate hydrogen peroxide, which then undergoes a Fenton reaction with ferrous ions in the system, producing hydroxyl radicals with extremely strong oxidizing power. These highly reactive hydroxyl radicals can effectively break the chemical bonds on the surface of hard and brittle workpieces, forming a softening layer, thereby significantly reducing the difficulty of mechanical material removal and improving processing efficiency. For example, invention patent CN118407109A discloses a silicon carbide wafer processing method based on an electrochemical-shear rheological composite effect, achieving a material removal rate of 255.5 nm / min for silicon carbide wafers through the synergistic effect of electrochemical corrosion and shear rheology. However, traditional electro-Fenton polishing technology still faces several technical bottlenecks: First, the process requires a large amount of polishing fluid containing electrolytes, which not only increases processing costs but may also cause environmental problems such as heavy metal pollution; second, the polishing process suffers from low abrasive utilization and poor dispersion uniformity, making it difficult to further improve processing efficiency; in addition, the iron sludge deposition generated during the reaction process can seriously affect the quality of the processed surface. Therefore, how to achieve a breakthrough in processing efficiency while ensuring processing accuracy and reducing environmental impact has become a key scientific problem and technical challenge that urgently needs to be solved in the field of precision machining of hard and brittle workpieces. Summary of the Invention
[0004] To overcome the aforementioned problems in the prior art, this invention provides a conductive gel abrasive with a ferrous sulfate slow-release function. This abrasive constructs a multi-layered mesh copper skeleton structure using three-dimensionally interwoven copper wires, upon which a mixed slurry is poured, giving the abrasive uniform conductive properties. The mixed slurry contains ferrous sulfate slow-release composite microparticles, prepared according to a specific component formula and following specific methods, possessing a unique "core-shell" structure: high specific surface area activated carbon acts as a carrier to adsorb ferrous sulfate as the reaction core, while the outer layer is coated with nano-silica using a sol-gel method to form a controllable release barrier. Using this conductive gel abrasive for electro-Fenton polishing offers advantages such as high polishing efficiency, low polishing fluid consumption, and low environmental pollution risk. Correspondingly, this invention also provides an electro-Fenton polishing method using the aforementioned conductive gel abrasive.
[0005] Regarding the grinding wheel, the technical solution of this application is as follows: A conductive gel abrasive with ferrous sulfate sustained-release function is prepared through the following steps: Step 1, 5-10g activated carbon powder, 5-10g ferrous sulfate powder, 10-15ml citric acid, and 20-30ml water are mixed and stirred to obtain mixed solution A; then 10-20 parts tetraethyl orthosilicate, 10-20 parts acetone, 20-30 parts deionized water, and 1-5 parts conductive carbon black are mixed and stirred to obtain mixed solution B, and acetic acid solution is added dropwise to mixed solution B to adjust its pH value to 4-6; then, mixed solution A is slowly added to mixed solution B and stirred in a water bath to complete the sol-gel process; then, after washing with anhydrous ethanol, it is ball-milled, sieved, and vacuum dried to obtain ferrous sulfate sustained-release composite microparticles; Step 2, an open-top square or rectangular mold is selected, and matrix-shaped holes are drilled at equal intervals on the opposite sidewalls of the mold. The positioning holes are arranged in a pattern; then, copper wires are threaded into the corresponding positioning holes along the X, Y, and Z axes respectively, forming a three-dimensional copper wire network structure inside the mold; the intersection of adjacent copper wires is insulated; in step 3, 5-10g of polyvinyl alcohol conductive hydrogel, 5-10g of modified phenolic resin, 40-60g of conductive copper powder, 10-20g of ferrous sulfate slow-release composite microparticles, 5-10ml of water, 0.1-0.5ml of initiator and 0.1-0.5ml of dispersant are mixed and stirred evenly to obtain a slurry; in step 4, the slurry is sieved and poured into the mold obtained in step 2, the top is sealed and placed in a refrigerator for low-temperature freezing, and after gelation, it is thawed and removed from the mold, then soaked in alcohol and dried, and finally placed in an oven for sintering and curing, and the conductive gel mold is completed.
[0006] Compared with existing technologies, the conductive gel abrasive with ferrous sulfate slow-release function of this application, through multi-scale structural design and functional modification, can achieve efficient and environmentally friendly polishing of hard and brittle workpieces, and has significant engineering application value in the field of precision machining. Specifically, the conductive gel abrasive of this application uses a three-dimensional copper wire network as a conductive skeleton, constructs a continuous electron transmission channel through a precision weaving process, and then casts a mixed slurry on this basis, giving the abrasive uniform conductive properties; wherein, the mixed slurry contains ferrous sulfate slow-release composite microparticles, which are prepared according to a specific component formula and a specific method step, and have a unique "core-shell" structure: high specific surface area activated carbon is used as a carrier to adsorb ferrous sulfate as the reaction core, and the outer layer is coated with nano-silica by a sol-gel method to form a controllable release barrier. When using the conductive gel abrasive of this invention for electro-Fenton polishing, mechanical shear force and chemical erosion selectively destroy the silica coating layer on the surface of the composite microparticles, realizing the gradient release of ferrous sulfate, and continuously providing ferrous ion catalyst for the electro-Fenton reaction; the released Fe 2+The H2O2 generated in situ at the cathode forms a homogeneous Fenton system, which generates a large number of highly active hydroxyl radicals at the polishing interface. These highly oxidizing active substances can quickly soften the surface of hard and brittle workpieces, forming a modified layer with a thickness of about 10-200 nm (at this time, the surface hardness of hard and brittle workpieces can be reduced by more than 50%), which is then scraped off by a conductive gel abrasive. This synergistic mechanism of surface softening and mechanical removal significantly improves the removal efficiency of hard and brittle workpieces.
[0007] Furthermore, in step 1, the concentration of the added acetic acid solution is 10-20 wt%, and the dropping rate is 1-2 drops / second; the sol-gel process is carried out at a stirring speed of 600-900 rpm and a water bath at 40-60℃ for a reaction time of 4-6 hours; after the reaction, it is washed 3-5 times with anhydrous ethanol, then ball-milled at 400-600 rpm for 4-6 hours, sieved, and vacuum-dried at 60℃-70℃ for 6-12 hours to finally obtain ferrous sulfate slow-release composite microparticles with uniform particle size distribution.
[0008] Furthermore, in step 2, the diameter of the positioning holes on the mold is 0.5–2 mm, and the spacing between adjacent positioning holes is 0.5–2 cm; 4–12 layers of copper wire are laid inside the mold along the X, Y, and Z axes, respectively, and the tension of each layer of copper wire is controlled at 5–8 N. Testing shows that the volume conductivity of the mold using the above structure can reach 4.6 × 10⁻⁶. 7 The S / m ratio can improve electron mobility by 1 to 2 orders of magnitude, and the network porosity is 60 to 70%, which provides ample space for subsequent gel filling.
[0009] Furthermore, in step 4, the slurry is first poured into a sieve to remove large agglomerates, and then poured into a mold. The sealed mold is placed in a refrigerator and frozen at a low temperature of -20 to -15°C for 4 to 8 hours. After gelation, it is taken out and thawed naturally at room temperature for 1 to 3 hours. Next, the copper wire at the edge of the gel is cut off, and the gel is removed from the mold and placed in a container containing alcohol to soak for 4 to 6 hours. Then, the gel is placed in a constant temperature and humidity chamber with a humidity of 20 to 30% and a temperature of 40 to 60°C to dry for 5 to 8 hours. Finally, the gel is placed in an oven and sintered and solidified at 120 to 160°C, and the conductive gel mold is completed.
[0010] Regarding the method, the technical solution of this application is as follows: An electro-Fenton polishing method is described, which utilizes the aforementioned conductive gel abrasive with ferrous sulfate slow-release function. The specific process is as follows: First, the workpiece to be processed is fixed on a fixture, and the conductive gel abrasive is mounted on the base plate of a surface polishing machine. The fixture is connected to the positive terminal of the power supply, and the conductive gel abrasive is connected to the negative terminal. Next, a cylinder drives the fixture to move downwards, bringing the workpiece into contact with the conductive gel abrasive. Then, a motor drives the conductive gel abrasive to rotate, causing relative sliding between the workpiece and the surface of the conductive gel abrasive. Simultaneously, the power is switched on, and polishing fluid is continuously dripped onto the processing area to perform electro-Fenton polishing on the workpiece. The polishing fluid is prepared by mixing 10-20 parts hydrogen peroxide, 80-100 parts water, and 0.1-0.2 parts hydrofluoric acid.
[0011] Furthermore, during the polishing process, the flow rate of the polishing slurry is 20–40 ml / min; the polishing pressure is 10–1000 kPa; the rotation speed of the conductive gel abrasive is 60–120 rpm; and the power supply voltage is 10–100 V.
[0012] Compared with existing technologies, the electro-Fenton polishing method of this application uses a conductive gel abrasive with a specific structure to achieve electro-Fenton polishing of hard and brittle materials, resulting in high polishing efficiency and less iron-containing sludge generation and environmental pollution. Specifically, the conductive gel abrasive employs a composite structure of a three-dimensional copper wire network conductive framework and a conductive modified gel matrix, and innovatively introduces core-shell structured ferrous sulfate slow-release composite microparticles, giving the abrasive uniform conductive properties and enabling the gradient release of ferrous sulfate to be triggered by mechanical action; during the polishing process, the Fe released by the abrasive... 2+ Under the electrolytic action of the polishing slurry, a Fenton reaction occurs with the H2O2 generated in situ at the cathode, producing a high concentration of hydroxyl radicals. This results in an easily removable softened layer on the workpiece surface, which is then mechanically removed by the abrasive, leading to high polishing efficiency. Furthermore, the continuous electrochemical reduction reaction at the cathode constantly reduces dissolved oxygen to H2O2, maintaining the supply of H2O2, while the Fe in the polishing slurry... 2+ It is then continuously oxidized to Fe 3+ Fe 3+ Under the influence of a DC electric field, it migrates to the cathode surface and is reduced back to Fe. 2+ Fe 3+ and Fe 2+ The circulation process ensures the continuous occurrence of the Fenton reaction, reduces the formation of iron sludge, lowers the risk of environmental pollution, and also reduces the amount of polishing fluid used. Experimental results demonstrate that this polishing method exhibits excellent processing efficiency for hard and brittle workpieces such as silicon carbide and sapphire, with a significantly higher material removal rate compared to traditional methods, resulting in good surface quality of the polished workpiece. Attached Figure Description
[0013] Figure 1This is a schematic diagram of the surface morphology and internal structure of the ferrous sulfate slow-release composite microparticles in the embodiments of this application; Figure 2 These are color change diagrams of three different sets of abrasives in the embodiments of this application before and after reacting with methyl orange in hydrogen peroxide solution; Figure 3 This is a schematic diagram of the electro-Fenton polishing principle in the embodiments of this application; Figure 4 It refers to the surface morphology and surface roughness of silicon carbide after electro-Fenton polishing; Figure 5 These are surface comparison images of silicon carbide before and after the electro-Fenton reaction; Figure 6 It is the microhardness of the silicon carbide surface before and after the electro-Fenton reaction; Figure 7 This is a graph showing the change in surface roughness of silicon carbide when using Fenton and electro-Fenton polishing. Figure 8 This is a graph showing the changes in material removal rate and surface roughness of silicon carbide during polishing at different voltages. Detailed Implementation
[0014] The present application will be further described below with reference to the accompanying drawings and embodiments, but this should not be construed as limiting the present application. Contents not described in detail in the following embodiments are all common knowledge in the art.
[0015] To improve the polishing efficiency of gel abrasives on hard and brittle workpieces and reduce environmental impact, this invention innovatively integrates the electro-Fenton reaction into the gel abrasive system. Specifically, this invention constructs a multi-layered mesh copper skeleton structure by three-dimensionally interwoven copper wires, and then casts a mixed slurry on this basis to form a novel gel abrasive with uniform conductive properties. Simultaneously, composite catalytic microparticles of ferrous sulfate coated with silica gel are added inside the abrasive. This abrasive combines the high-efficiency processing characteristics of bonded abrasives with the precise surface treatment capabilities of free abrasives, enabling precise spatial coupling of electro-Fenton catalytic reaction and mechanical polishing. This forms a synergistic "chemical softening-mechanical removal" mechanism at the microscale, resulting in a qualitative leap in the removal efficiency of hard and brittle workpieces. Secondly, its unique core-shell slow-release structure significantly improves the utilization rate of iron catalysts, reduces iron ion loss, and minimizes the formation of iron sludge, effectively reducing environmental pollution risks. Thirdly, the integrated slow-release catalytic system and conductive network design within the abrasive reduce the amount of polishing fluid used by more than 70%, achieving environmentally friendly near-dry green processing and reducing wastewater treatment costs. Example
[0016] The conductive gel abrasive with ferrous sulfate slow-release function in this embodiment is prepared by the following steps.
[0017] Step 1: Prepare ferrous sulfate slow-release composite microparticles. The specific process is as follows.
[0018] Step 1.1: Mix 10g of activated carbon powder with a particle size of 3000 mesh, 10g of ferrous sulfate powder, 15ml of citric acid and 30ml of water to obtain mixed solution A. The stirring speed is 700 rpm and the pH value of mixed solution A is 4.
[0019] In this process, the porous structure of activated carbon can effectively adsorb ferrous sulfate, reducing the contact area between ferrous sulfate and water; citric acid, through its carboxylic acid groups, reacts with Fe... 2+ It forms a stable complex while maintaining the pH value of the system and inhibiting the hydrolysis reaction of ferrous sulfate.
[0020] Step 1.2: Mix 20wt% tetraethyl orthosilicate, 20wt% acetone, 55wt% deionized water and 10wt% conductive carbon black to obtain mixed solution B. Add 10wt% acetic acid solution to mixed solution B to adjust its pH value at a dropping rate of 2 drops / second. When the pH value of mixed solution B stabilizes at 5, slowly add mixed solution A to mixed solution B and react for 5 hours under stirring speed of 700 rpm and water bath conditions of 60℃ to complete the sol-gel process.
[0021] Step 1.3: After the reaction is complete, the gel product is washed three times with anhydrous ethanol to remove unreacted tetraethyl orthosilicate and byproducts. Then, it is ball-milled at 600 rpm for 6 hours and sieved through a 200-mesh sieve. Finally, the sieved product is vacuum-dried at 60°C for 6 hours to obtain ferrous sulfate sustained-release composite microparticles with uniform particle size distribution (surface morphology and internal structure as shown in Figure 1). Figure 1 (As shown).
[0022] The composite microparticles obtained through the above steps are coated with a silica layer, which effectively blocks water molecule contact and prevents the iron catalyst from dissolving in water. The doped conductive carbon black forms a three-dimensional conductive network within the silica sol matrix, effectively improving the conductivity of the silica sol. During subsequent polishing, mechanical friction and chemical action selectively disrupt the local silica coating, enabling the controlled release of ferrous ions and ensuring the density of active sites at the electro-Fenton reaction interface, thereby increasing the efficiency of hydroxyl radical generation. This structural design avoids premature loss of the iron catalyst and enhances the electro-Fenton reaction rate by increasing the reaction contact area.
[0023] To verify the performance of the composite microparticles, abrasives containing ferrous sulfate particles and ferrous sulfate slow-release composite microparticles were immersed in hydrogen peroxide solution, designated as Group 1 and Group 3; abrasives containing ferrous sulfate slow-release composite microparticles were immersed in hydrogen peroxide solution containing 0.1 wt% hydrofluoric acid, designated as Group 2. Then, methyl orange was added to each of the three solutions and allowed to stand for 1 hour (see...). Figure 2 a) Methyl orange is consumed by hydroxyl radicals, and its fading color reflects the rate of the Fenton reaction. Figure 2 As shown in b, the color of group 1 remained almost unchanged, while the methyl orange in groups 2 and 3 changed from orange to yellow, indicating a faster Fenton reaction rate. In group 3, due to weak protection of the ferrous sulfate particles, they quickly dissolved in water, resulting in a high rate of iron catalyst loss and a weak reaction on the grinding wheel surface with no bubble formation. In contrast, group 2 had a water-resistant silica sol on the surface of the composite particles. This sol layer was selectively destroyed by hydrofluoric acid, slowly releasing ferrous sulfate. The iron catalyst loss rate was low, and the particles on the grinding wheel surface continuously participated in the reaction, generating continuous bubbles. Therefore, it can be concluded that the silica sol on the outer layer of the composite particles effectively protects the internal ferrous sulfate, preventing it from easily hydrolyzing and reducing Fe... 2+ The loss rate is reduced; at the same time, after the surface is damaged, it can slowly provide iron catalyst to participate in the Fenton reaction, thus improving the utilization rate of iron catalyst.
[0024] Step 2: Construct a three-dimensional copper wire network mold. The specific process is as follows.
[0025] Step 2.1: Select a 10cm×10cm×5cm open square mold (made of polytetrafluoroethylene or polypropylene); drill positioning holes with a diameter of 0.5mm at equal intervals of 1cm on opposite sidewalls of the mold, with the holes arranged in a matrix to ensure that the horizontal and vertical channels are strictly aligned.
[0026] Step 2.2: Using high-purity copper wire with a diameter of 50μm, the wires are sequentially threaded through the corresponding holes along the X-axis using a wire-threading device. The spacing between each layer of copper wire is maintained at 1cm, and a total of 4 layers are laid to form a dense transverse conductive network. After completing the transverse network, the mold is rotated 90°, and the same process is used to lay 4 and 9 layers of copper wire networks along the Y-axis and Z-axis, respectively. The tension of each layer of copper wire is controlled at 5–8N to ensure the stability of the network structure. Insulation is applied at the intersections of the copper wires using micro-polyimide gaskets to prevent short circuits. Through XYZ triaxial orthogonal weaving, a three-dimensional interpenetrating network structure is finally formed, and the three-dimensional copper wire network mold is completed. Testing shows that the volume conductivity of this mold can reach 4.6 × 10⁻⁶. 7 The S / m ratio improved electron mobility by an order of magnitude; the network porosity was 70%, leaving ample space for subsequent gel filling.
[0027] Step 3: Mix 10 wt% polyvinyl alcohol conductive hydrogel, 8 wt% modified phenolic resin, 52 wt% conductive copper powder, 20 wt% ferrous sulfate slow-release composite microparticles, 10 wt% water, 0.1 wt% initiator, and 0.1 wt% dispersant in a beaker and stir at 900 rpm for 1 hour until homogeneous to obtain a slurry. The polyvinyl alcohol conductive hydrogel is made by adding conductive carbon black to polyvinyl alcohol to improve its conductivity; polyvinyl alcohol has the ability to gel at low temperatures. The modified phenolic resin improves its insulation properties by doping with graphene. The ferrous sulfate slow-release composite microparticles serve as a solid-phase catalyst for the electro-Fenton reaction.
[0028] Step 4: The slurry is finely filtered through a 325-mesh stainless steel sieve to effectively remove agglomerated particles larger than 50μm, ensuring slurry uniformity (the sieving process is carried out in a clean environment, with the sieve tilted at 60° to optimize filtration efficiency); the sieved slurry is poured into the mold prepared in Step 2, with the pouring speed controlled at 5mL / min to avoid air bubble formation; after sealing the top of the mold using vacuum sealing technology, it is immediately transferred to a -20℃ low-temperature refrigerator for cryogeling, maintaining it for 8 hours to ensure complete phase separation and network structure formation; after gelation, the mold is placed at room temperature for natural thawing for 2 hours to allow the ice to thaw. The crystals melt to form a porous structure; after thawing, the copper wire connection points at the edge of the gel are cut off with precision pliers, and the complete gel body is carefully removed; the gel is immersed in anhydrous ethanol solution for 6 hours, and fresh ethanol is replaced every 2 hours to gradually remove water by solvent displacement. This process can maintain the porous structure of the gel and avoid drying shrinkage and deformation; the sample is then transferred to a constant temperature and humidity chamber (temperature 40℃, relative humidity 20%) for the first stage of drying, which lasts for 8 hours to slowly remove residual solvent. Subsequently, it is heat-cured in a 160℃ forced-air drying oven for 2 hours, with the heating rate controlled at 2℃ / min, so that the polymer is fully cross-linked and cured, and the conductive gel mold is completed.
[0029] See Figure 3In this embodiment, the inventors used the aforementioned conductive gel abrasive with ferrous sulfate slow-release function to perform electro-Fenton polishing on a silicon carbide workpiece with a surface roughness of 60nm. The specific process is as follows: The silicon carbide workpiece to be processed is bonded and fixed on a special fixture using high-temperature paraffin (the adhesive layer thickness is controlled at 100-200μm to ensure conductivity and stability). The conductive gel abrasive is mounted on the base plate of a surface polishing machine (the conductive gel abrasive is first precisely trimmed), with the fixture connected to the positive terminal of the power supply and the conductive gel abrasive connected to the negative terminal (using a pulsed DC power supply, voltage adjustable from 0-100V). Next, the fixture is driven by a cylinder to move downwards, bringing the workpiece into contact with the conductive gel abrasive. Then... The conductive gel abrasive is driven by a motor to rotate at 80 rpm, causing relative sliding between the workpiece and the surface of the conductive gel abrasive. At the same time, the power is turned on and polishing fluid is continuously dripped into the processing area at a flow rate of 24 ml / min to perform electro-Fenton polishing on the workpiece at a polishing pressure of 11 kPa. The polishing fluid is prepared by mixing 19.9 wt% hydrogen peroxide, 80 wt% water and 0.1 wt% hydrofluoric acid (wherein, hydrogen peroxide can increase the Fenton reaction rate, and a small amount of hydrofluoric acid can dissolve the silica sol particles on the surface of the ferrous sulfate slow-release composite microparticles, realizing the controlled release of ferrous sulfate, and can also adjust the pH of the polishing environment to an acidic environment to reduce the generation of iron sludge).
[0030] See Figure 4 After polishing a silicon carbide workpiece for 60 minutes, its surface roughness decreased to 5.7 nm. Specifically, after 30 minutes of electro-Fenton polishing, a uniform oxide-modified layer was formed on the silicon carbide surface under the strong oxidizing effect of hydroxyl radicals (see...). Figure 5 Microhardness testing of the modified layer using a nanoindenter revealed that after 30 minutes of polishing, the average surface microhardness of silicon carbide decreased from the initial 3621.3 HV to 3290.2 HV (e.g., ...). Figure 6 As shown in the figure, this phenomenon can be attributed to the formation of a modified oxide layer with relatively low hardness on the surface due to the electro-Fenton oxidation process. As the polishing time continues to increase, the microhardness value of the substrate material can be basically restored to the original level after the surface modified layer is gradually removed. This reversible change process confirms that the effect of electro-Fenton polishing on the bulk properties of the material is limited to the surface area.
[0031] Comparative experiment: To verify that the polishing method of this invention has higher polishing efficiency, the inventors conducted a comparative experiment between electro-Fenton polishing and Fenton polishing. In the first group, a gel abrasive without a three-dimensional copper mesh framework and ferrous sulfate slow-release composite particles was used with a Fenton polishing solution (10wt% ferrous sulfate, 10wt% hydrogen peroxide, pH=4) to polish silicon carbide. The gel abrasive was not connected to a power source during polishing. In the second group, the conductive gel abrasive of this invention was used with a Fenton polishing solution (10wt% hydrogen peroxide, pH=4) to polish silicon carbide. The conductive gel abrasive was connected to a power source with a DC voltage of 10V during polishing. The initial surface roughness of the silicon carbide was 60nm.
[0032] Two groups underwent polishing experiments. The polishing time was 60 minutes, and the polishing fluid flow rate was 24 ml / min. The results are as follows: Figure 7 As shown, the surface roughness Sa of silicon carbide after polishing with the conductive gel abrasive prepared according to the present invention in the second group reached 5.7 nm, which is much higher than the surface roughness Sa of silicon carbide after Fenton polishing in the first group (11.2 nm). This difference is because DC voltage can drive Fe 2+ / Fe 3+ The cyclic regeneration significantly increases the generation rate of hydroxyl radicals (·OH); at the same time, the conductive gel abrasive mold makes the oxidation reaction more concentrated in the contact area, avoiding global over-corrosion.
[0033] In addition, the inventors also conducted experiments to measure the material removal rate and surface roughness of the workpiece surface under different voltage intensities in the polishing area. For example... Figure 8 As shown, the material removal rate exhibits a monotonically increasing trend as the applied voltage gradually increases from 0 V to 25 V. This phenomenon is mainly attributed to the fact that the voltage increase significantly enhances the kinetics of the electro-Fenton reaction, promoting the removal of Fe. 2+ / Fe 3 + The redox cycle increases the generation rate of hydroxyl radicals, and the higher electrode potential accelerates the formation of the oxide layer on the silicon carbide surface, thereby improving the mechanical removal efficiency. However, the surface roughness Sa exhibits a non-monotonic change with voltage: in the range of 0–10 V, the Sa value gradually decreases from an initial 9.8 nm to 5.7 nm; when the voltage exceeds 15 V, the Sa value actually increases. This is because excessively high voltage leads to excessive local current density in the abrasive and polishing slurry, causing uneven oxidation of the silicon carbide surface, forming pits, and resulting in a decrease in surface quality. In actual polishing processes, the rate and extent of the electro-Fenton reaction can be controlled by adjusting the voltage.
[0034] The foregoing general description of the invention and its specific embodiments should not be construed as limiting the technical solution of the invention. Those skilled in the art, based on the disclosure of this application, can add, reduce, or combine the disclosed technical features in the foregoing general description and / or embodiments without departing from the constituent elements of the invention, to form other technical solutions within the scope of protection of this application.
Claims
1. A conductive gel abrasive with ferrous sulfate slow-release function, characterized in that, The conductive gel abrasive is prepared by the following steps: Step 1: Mix 5-10g activated carbon powder, 5-10g ferrous sulfate powder, 10-15ml citric acid, and 20-30ml water to obtain mixed solution A. Then, mix 10-20 parts tetraethyl orthosilicate, 10-20 parts acetone, 20-30 parts deionized water, and 1-5 parts conductive carbon black to obtain mixed solution B. Add acetic acid solution dropwise to mixed solution B to adjust its pH value to 4-6. Next, slowly add mixed solution A to mixed solution B and stir in a water bath to complete the sol-gel process. Then, wash with anhydrous ethanol, ball mill, sieve, and vacuum dry to obtain ferrous sulfate slow-release composite microparticles. Step 2: Select a capless square or rectangular mold and drill positioning holes in a matrix arrangement at equal intervals on opposite sidewalls of the mold; then insert copper wires into the corresponding positioning holes along the X-axis, Y-axis and Z-axis directions respectively to form a three-dimensional copper wire network structure inside the mold. Step 3: Mix 5-10g of polyvinyl alcohol conductive hydrogel, 5-10g of modified phenolic resin, 40-60g of conductive copper powder, 10-20g of ferrous sulfate slow-release composite microparticles, 5-10ml of water, 0.1-0.5ml of initiator and 0.1-0.5ml of dispersant to obtain a slurry; Step 4: After sieving the slurry, pour it into the mold prepared in Step 2, seal the top, and place it in a refrigerator for low-temperature freezing. After gelation, thaw it and remove the gel from the mold. Then, soak it in alcohol and dry it. Finally, put it in an oven for sintering and curing. The conductive gel mold is now ready.
2. The conductive gel abrasive with ferrous sulfate slow-release function according to claim 1, characterized in that: In step 1, the sol-gel process is carried out at a stirring speed of 600-900 rpm and a water bath temperature of 40-60°C for a reaction time of 4-6 hours.
3. The conductive gel abrasive with ferrous sulfate slow-release function according to claim 2, characterized in that: In step 1, after the sol-gel reaction is completed, the particles are washed 3 to 5 times with anhydrous ethanol, then ball-milled at 400 to 600 rpm for 4 to 6 hours, sieved, and then vacuum-dried at 60°C to 70°C for 6 to 12 hours to finally obtain ferrous sulfate slow-release composite microparticles with uniform particle size distribution.
4. The conductive gel abrasive with ferrous sulfate slow-release function according to claim 3, characterized in that: In step 1, the concentration of the acetic acid solution added is 10-20 wt%, and the dropping rate is 1-2 drops / second.
5. The conductive gel abrasive with ferrous sulfate slow-release function according to claim 1, characterized in that: In step 2, 4 to 12 layers of copper wire are laid inside the mold along the X-axis, Y-axis and Z-axis directions, and the tension of each layer of copper wire is controlled at 5 to 8 N.
6. The conductive gel abrasive with ferrous sulfate slow-release function according to claim 5, characterized in that: The diameter of the positioning holes on the mold is 0.5 to 2 mm, and the distance between two adjacent positioning holes is 0.5 to 2 cm.
7. The conductive gel abrasive with ferrous sulfate slow-release function according to claim 1, characterized in that: In step 4, the slurry is first poured into a sieve to remove large agglomerates, and then the slurry is poured into a mold.
8. The conductive gel abrasive with ferrous sulfate slow-release function according to claim 7, characterized in that: In step 4, the encapsulated mold is placed in a refrigerator and frozen at a low temperature of -20 to -15°C for 4 to 8 hours until gelation occurs. After gelation, the mold is removed and allowed to thaw naturally at room temperature for 1 to 3 hours. Next, the copper wires at the edge of the gel are cut off, and the gel is removed from the mold and placed in a container containing alcohol for 4 to 6 hours. Then, the gel is placed in a constant temperature and humidity chamber with a humidity of 20 to 30% and a temperature of 40 to 60°C for 5 to 8 hours to dry. Finally, the gel is placed in an oven and sintered and solidified at 120 to 160°C, thus completing the preparation of the conductive gel mold.
9. An electro-Fenton polishing method, characterized in that: This method utilizes the conductive gel abrasive with ferrous sulfate slow-release function as described in claim 1. The specific process is as follows: First, the workpiece to be processed is fixed on a fixture, and the conductive gel abrasive is mounted on the base plate of a surface polishing machine. The fixture is connected to the positive terminal of the power supply, and the conductive gel abrasive is connected to the negative terminal. Next, the fixture is driven to move downward by a cylinder, so that the workpiece comes into contact with the conductive gel abrasive. Then, the conductive gel abrasive is driven to rotate by a motor, so that the workpiece and the surface of the conductive gel abrasive slide relative to each other. At the same time, the power is turned on, and polishing liquid is continuously dripped into the processing area to perform electro-Fenton polishing on the workpiece. The polishing liquid is obtained by mixing 10-20 parts of hydrogen peroxide, 80-100 parts of water, and 0.1-0.2 parts of hydrofluoric acid.
10. The electro-Fenton polishing method according to claim 9, characterized in that: During the polishing process, the flow rate of the polishing slurry is 20–40 ml / min; the polishing pressure is 10–1000 kPa; the rotation speed of the conductive gel abrasive is 60–120 rpm; and the power supply voltage is 10–100 V.
Citation Information
Patent Citations
Polyvinyl alcohol acetal resin grinding tool based on organic gel forming method
CN108081159A
Method for preparing vitrified bonded grinding tool realizing high-precision polishing by adopting gel casting process
CN112123223A
High-porosity ceramic bond diamond micro-powder grinding tool as well as preparation method and application thereof
CN120038677A
Fenton-assisted three-phase flowing pressure cavitation polishing SiC optimal curved surface method and device
CN108581817A
Chemical mechanical polishing device for silicon carbide wafer
CN115106929A